Projeto "uma vaca para o índio": perspectiva social na prática pastoral diocesana (Roraima, 1970-1996) - Cavalcante, Ronalson Moura (2015)
The research had as scope to examine indigenous pastoral practice of the Roman Catholic Church that settles in a social and perspective, which tries to materialize specifically the Project "A cow for the Indian." It's not purpose of this study present the indian point of view towards the cattle project. Despite efforts lack us the domain of an updated anthropological language, resultant of my degree in history. The interpretative analysis of the biblical scriptures, guided by the Second Vatican Council, endorsed and deepened by the documents of the bishops of Latin America in its clear preference for the poor, guided the pastoral actions to this line of action. Thus, the purpose was to understand nuances of a visibly rooted pastoral action in an ecclesiological adverse model, to the model to be Church, until now guided by the parameters of the Council of Trent, and evidenced on a theology focused on the reality and deliverance to the oppression of condition in which was encountered most of the people in Latin America, in this case the Indians. In this perspective, the Diocese Roraima of contributed to the preparation of documents for meetings, committees and councils that participated and thus committed itself to the construction of the justice, engaging itself in the renewal of indigenous pastoral. The project "A cow for the Indian" was a strategy that fundamentally contributed to the approval of indigenous lands, especially of the Raposa Serra do Sol, and modified the relations between Indians and non-Indians to constitute the material basis of indigenous organization promoting, in part, it's political and economic independence. This research, socio-religious character, tried to answer the theme of the importance of institutional religious factors at the time that interfere with social, economic and political; for both, we going through the Amazon historiography, with snip in Roraima. In this sense, the case study included literature reviews, interviews, research in journals, newspapers and magazines, documentary records (meeting minutes, reports, pastoral letters and pamphlets).